إشكالية تدبّر المتلقي في النص القرآني (Journal of Imam Al-Kadhim College, 2023)
This study makes an effort to raise questions that are prompted by the contemplative method that the Holy Qur'an recommends, regarding it as a defense of creation. Instead, it separated the two types of responses to the Qur'anic text into two categories: closed-hearted and reflective. Do they not think about the Qur'an, or are their hearts locked up? This issue raises the following queries: What duty do We have toward the Quranic text? Is it possible for someone to understand the Qur'an purely via contemplation? What are the techniques for contemplation? Exist any requirements for someone to be considered prudent? Do the wise take into account interpreter? What connection exists between contemplation and interpretation? Is there a connection between meditation and what the Prophet (may Allah bless him and his family) meant when he said that he would bring his words, his deeds, and his choice to the Book of Allah Almighty? How can thought be kept from being influenced by interpretation or opinion? Through its investigation, the study will attempt to provide answers to these concerns and matters relevant to them.
Keywords: الكلمات المفتاحية : النصّ، المتلقي، المتدبّر.